Revealing the role of magnetic materials in light-driven advanced oxidation processes: enhanced degradation of contaminants and facilitated magnetic recovery - González-Fernández, Cristina; Bringas, Eugenio; Rivero, María J.; Ortiz, Inmaculada (Frontiers in Chemical Engineering, 2024)
Semiconductor photocatalysis, heterogeneous photo-Fenton and heterogeneous photocatalytic persulfate activation are light-driven advanced oxidation processes (AOPs) that have attracted much attention as promising technologies in wastewater treatment. Nevertheless, their large-scale application still faces several challenges, including the need to separate the catalyst from the treated water. In this regard, composite catalysts made up of semiconductor and magnetic materials have been understood as a potential alternative since the resulting magnetic photocatalysts can be easily separated from the medium by applying an external magnetic field. Interestingly, apart from facilitating the photocatalyst retrieval, the magnetic components could also be involved in the photocatalytic process. However, while the magnetic separation ability has been widely highlighted, other functions of the magnetic constituents remain obscure. This work, which covers the last six years of research, provides a comprehensive review on the magnetically assisted photocatalytic degradation of organic pollutants from water. Specifically, the magnetic photocatalysts that are commonly employed for that purpose are presented and the different roles of their magnetic constituents (roughly grouped as retrieval assistance, active catalyst, conduction medium or activator) are discussed. Furthermore, the importance of designing magnetic separators for attaining the photocatalyst retrieval is also emphasized. Collectively, this study could supply an avenue for developing magnetic photocatalysts that take advantage of both roles of magnetic materials, which can contribute to accomplish a more efficient pollutant degradation.